OUTPUT AND EMPLOYMENT OF MANUFACTURING SECTOR IN CENTRAL JAVA PROVINCE: SOURCES OF GROWTH AND MULTIPLIER USING THE I-O TABLES IN 2000 AND 2008 - , AIDZIN ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The economy of Central Java was mostly supported by the manufacturing sector. It has been one of the main driving forces since its share on total output growth of Central Java was more than 34 percent during the 2000-2008 period. This sector was also able to absorb almost 17 percent of total employment in 2008. The thesis examines the sources of output and employment growth focusing on the manufacturing sector in Central Javaâs economy over 2000-2008 using a decomposition method within the input-output (IO) framework. The model uses two comparable IO tables for 2000 and 2008 as the main data sources and accounts for output and employment changes from the demand side. The output growth is decomposed into domestic demand expansion, technological change, export expansion and import substitution, while the growth of employment is decomposed into domestic demand expansion, technological change, export expansion, import substitution and employment coefficient change. Second objective is to examines output and employment multiplier for the same sector. In addition, the last objective of this study is to know policy implications of development in manufacturing sector on economy of Central Java. The result shows that most of the output growth of the manufacturing sector was caused by the effect of import substitution (IS), followed by household consumption (DD1) and export expansion (EE), while import substitution (IS) played a significant role in the employment growth, followed by household consumption (DD1) and government consumption (DD2). In terms of multiplier, food, beverages and tobacco, and wood products were two subsectors that had relatively high output and employment multiplier. Policies implemented for developing industrial sector give positive implications on economy of Central Java, i.e. the increase of number of population in industrial sector, particularly, small and medium scale industry. It will increase output of industrial sector and increase economic growth in Central Java. Moreover, the increase of number of small and medium scale industry will increase job opportunity and reduce unemployment and poverty in Central Java.